Pengaruh Penggunaan LKPD Berbasis STEM terhadap Peningkatan Kemampuan Berfikir Kreatif Peserta Didik pada Materi Bumi dan Tata Surya di SMP Negeri 2 Kutalimbaru - Fadhila, Dita; Djulia, Ely; Bangun, Putri Sion (Unnes Physics Education Journal, 2024)
This research aims to determine the effect of using STEM-based LKPD on improving students' creative thinking abilities on earth and solar system material at SMP Negeri 2 Kutalimbaru. This research is a type of quasi-experimental research that uses a non-equivalent control group design, namely a design that provides a pretest prior to treatment and a posttest subsequent to treatment. The population in this study were all students in class VII of SMP Negeri 2 Kutalimbaru. The sampling technique used in this research was purposive sampling use 60 students as samples. The sample consisted of two classes, namely class VII-1 as the experimental class which was treated using STEM-based LKPD, and class VII-2 as the control class. Data was collected through observation, teacher interviews, and creative thinking ability tests. The research results were then analyzed using normality tests, homogeneity tests, and hypothesis tests assisted by IBM SPSS Statistics 29.0 for windows. The hypothesis result is Sig.0.001 with a significance level (α) = 0.05. It is stated that 0.001 < 0.05, so a decision can be made that Ha is accepted and Ho is rejected. There is an influence of using STEM-based LKPD on increasing students' creative thinking abilities on earth and solar system material. The ability to think creatively and flexibly (Flexibility) experienced the highest increase. This can be stated based on the N-gain results for this indicator of 91.18.